Напрями підвищення ефективності складської логістики - Багорка, Марія Олександрівна; Bahorka, Mariia; Якубенко, Юлія Леонідівна; Yakubenko, Yuliia (Університет економіки і підприємництва, 2023)
В статті визначена роль логістичної діяльності компаній в сучасних умовах, надана характе-ристика складської логістики, її основних складових та сформовано пропозиції щодо підвищення її ефек-тивності складської логістики відповідно до сучасних вимог ведення бізнесу. Виокремлено основні про-блеми на ринку складської нерухомості в Україні. Зазначено, що в умовах глобалізації логістичних процесів діджиталізація та аутсорсинг стають все більш актуальними, а впровадження складської логістики в ком-паніях розширює сегмент ринку та завойовує нових клієнтів. Доведено, що складська логістика в сучасних умовах досягається шляхом самостійного створення, придбання та управління програмним забезпеченням LMS, або шляхом аутсорсингу та залучення зовнішньої логістичної компанії (3PL). Аутсорсинг бере на себе всі логістичні процеси за вас. Показано, що використання 3PL прискорює етап впровадження, не вимагаючи навчання персоналу новим процесам, обладнанню та програмному забезпеченню. The article defines the role of logistics activities of companies in modern conditions, provides a description of warehouse logistics, its main components, and formulates proposals for improving the ef-ficiency of warehouse logistics in accordance with modern business requirements. Warehouse logistics is the organization, planning and management of warehouses, its tasks and functions are fast and timely movement and delivery of goods to their destination. This requires a modern and reliable infrastructure in the form of an appropriately equipped warehouse complex. The main principle when creating a storage system is an indi-vidual solution that takes into account all factors and ensures the economic efficiency of the warehouse. The goal of warehouse logistics is the development of a storage system that allows optimal distribution of goods in the warehouse and rational management of these goods. The warehouse complex plays an important role in the work of a modern logistics company. The efficiency of work and the developed infrastructure of the warehouse complex directly affect the uninterrupted operation of the enterprise and its competitiveness in the market. The main problems in the warehouse real estate market in Ukraine are highlighted. It is noted that in the condi-tions of globalization of logistics processes, digitalization and outsourcing are becoming more and more rel-evant, and the implementation of warehouse logistics in companies expands the market segment and wins new customers. In modern conditions, digitalization of warehouse logistics occurs due to: independent creation, acquisition and management of ALS software; outsourcing – using an external logistics company (3PL) to per-form all logistics operations for you. With a 3PL, you can shorten the implementation phase without having to train your employees on new processes, equipment, and software. It has been proven that warehouse logistics in modern conditions is achieved by independently creating, purchasing and managing LMS software, or by outsourcing and involving an external logistics company (3PL). Outsourcing takes over all logistics processes for you. Using a 3PL has been shown to speed up the implementation phase without requiring personnel to be trained in new processes, equipment and software.
Directions of improving the efficiency of warehouse logistics
Keywords: логістика; logistics; складська логістика; warehouse logistics; система управління; management system; процесний підхід; process approach; логістична система; logistics system; цифровізація; digitalization; аутсорсинг; outsourcing